Aortic and Mitral Valve Replacement Through a Single Transverse Aortotomy: A Useful Approach in Difficult Mitral Valve Exposure - Carmichael, Michael J. (1983)
Replacement of the mitral valve through a standard vertical left atriotomy in patients requiring both aortic and mitral valve replacement can be very difficult. This is especially true in patients who have undergone previous median sternotomy. Replacement of the mitral valve through the aortic root after excision of the aortic valve is described in two case reports. This is a convenient approach when traditional exposure of the mitral valve is impractical in patients requiring double valve replacement.